2011
DOI: 10.1002/mnfr.201000548
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesion as a functional concept for prevention of pathogens: N‐Phenylpropenoyl‐L‐amino acid amides as inhibitors of the Helicobacter pylori BabA outer membrane protein

Abstract: The nutritional use of NPA-containing food may justify a positive antiadhesive effect against the recurrence of H. pylori infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Furthermore the aspartic acid amide of caffeic acid (Caff-Asp) showed strong antiadhesive properties against the adhesion of Helicobacter pylori to human stomach tissue (Hensel et al, 2007). It was shown that NPA interact with the H. pylori outer membrane protein BabA (Niehues, Stark, Keller, Hofmann, & Hensel, 2011). Preliminary data on the occurrence and bioactivity in food and medicinal plants (Hensel et al, 2007; and on intestinal absorption and bioavailability in humans (Stark, Lang, Keller, Hensel, & Hofmann, 2008) are available.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore the aspartic acid amide of caffeic acid (Caff-Asp) showed strong antiadhesive properties against the adhesion of Helicobacter pylori to human stomach tissue (Hensel et al, 2007). It was shown that NPA interact with the H. pylori outer membrane protein BabA (Niehues, Stark, Keller, Hofmann, & Hensel, 2011). Preliminary data on the occurrence and bioactivity in food and medicinal plants (Hensel et al, 2007; and on intestinal absorption and bioavailability in humans (Stark, Lang, Keller, Hensel, & Hofmann, 2008) are available.…”
Section: Introductionmentioning
confidence: 97%
“…From these results it is assumed that the polysaccharide may interact with the immunological system. Some pre-and probiotics interact with the bacterial adhesion of pathogens to the eukaryotic binding receptors throughout so called antiadhesive compounds [29][30][31][32][33]. In case of pretreatment of AGS cells with EPS1190 the polysaccharide was shown to inhibit H. pylori adhesion by interaction with the surface of AGS cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…It seems interesting that inhibition of the Arg‐gingipain proteases in our in vitro study leads to a feed back mechanism of increased gene expression for rgp A, which indicates that the gingipain activity is controlled by bacterial cellular programmes. Recent studies on correlation of Helicobacter pylori adhesion with the gene expression for the respective OMP adhesins showed that the adhesion process for H. pylori is not related to changes in gene expression of the adhesins and virulence factors (Niehues et al 2010a). In contrast, P. gingvalis seems to have a gene regulation system, which correlates gene expression with gingipain protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that P. gingivalis cell adhesion predominantly relies on the functions of gingipain proteases, the use of anti‐adhesive compounds influencing protein–protein interactions should be favoured. In contrast, carbohydrate–protein interactions, as known for other adhesive gram‐negative bacteria (Niehues et al 2010a), are less important for P. gingivalis binding to eukaryotic cells (M. Niehues, T. Stark, D. Keller, T. Hofmann, A. Hensel unpublished data). Manipulation of the P. gingivalis OMP functions can be achieved either by soluble, exogenous modified substrates of the gingipains, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation